POWER, PERSUASION, AND CONSUMER IDENTITY: A CRITICAL DISCOURSE ANALYSIS OF MCDONALD’S ADVERTISEMENT CALLED ‘SELF-CONTROL, WHO?’ - Amzelina Risty Br. Lubis, Aliffa; Jayanti; Izhar Maulana, Alif; Zein, T. Thyrhaya (Dialectical Literature and Educational Journal, 2024)
The purpose of this research is to analyze power, persuasion, and consumer identity McDonald's advertisements in terms of critical discourse analysis techniques. Research focus on persuasiveness has been popular for a long time, studied as the art of speaking and features of rhetoric. Linguists have never stopped in their quest to find out what linguistic elements create persuasive effects and impact human brains to convince people about something. The research aimed by applying CDA to this advertisement, research seeks to uncover how McDonald's uses discourse as a tool for ideological persuasion and how it constructs a consumer identity aligned with contemporary values of individualism and freedom of choice. This study adopts a qualitative research design to analyze McDonald’s "Self-Control, Who?" advertisement using Critical Discourse Analysis (CDA). Data for this analysis was collected directly from McDonald's "Self-Control, Who?" advertisement, which was selected based on its relevance and representativeness of the brand's broader advertising strategy. The results of the study show that McDonald's "Self-Control, Who?" advertisement is not just about selling a product—it is a tool for promoting a lifestyle and set of values that prioritize immediate pleasure, convenience, and individual choice. By analyzing this ad through Fairclough’s CDA framework, we uncover how such advertisements play a significant role in constructing ideologies, reinforcing power relations, and shaping the cultural landscape of modern consumerism